The sustainable urban development reader - Wheeler, Stephen M., 1957-; Beatley, Timothy, 1957- (2014)
"Building on the success of its second edition, the third edition of the Sustainable Urban Development Reader provides a generous selection of classic and contemporary readings giving a broad introduction to this topic. It begins by tracing the roots of the sustainable development concept in the nineteenth and twentieth centuries, before presenting readings on a number of dimensions of the sustainability concept.Topics covered include land use and urban design, transportation, ecological planning and restoration, energy and materials use, economic development, social and environmental justice, and green architecture and building. All sections have a concise editorial introduction that places the selection in context and suggests further reading. Additional sections cover tools for sustainable development, international sustainable development, visions of sustainable community and case studies from around the world. The book also includes educational exercises for individuals, university classes, or community groups, and an extensive list of recommended readings.The anthology remains unique in presenting a broad array of classic and contemporary readings in this field, each with a concise introduction placing it within the context of this evolving discourse. The Sustainable Urban Development Reader presents an authoritative overview of the field using original sources in a highly readable format for university classes in urban studies, environmental studies, the social sciences, and related fields. It also makes a wide range of sustainable urban planning-related material available to the public in a clear and accessible way, forming an indispensable resource for anyone interested in the future of urban environments"--
"Building on the success of its second edition, the third edition of the Sustainable Urban Development Reader offers an unrivalled selection of classic and contemporary readings and case studies providing a broad introduction to this key topic. It begins by tracing the roots of the sustainable development concept in the nineteenth and twentieth centuries, before presenting readings on a number of dimensions of the sustainability concept. Topics covered include land use and urban design, transportation, ecological planning and restoration, energy and materials use, economic development, social and environmental justice, and green architecture and building. All sections have a concise editorial introduction that places the selection in context and suggests further reading. Additional sections cover tools for sustainable development, sustainable development internationally, visions of sustainable community and case studies from around the world. The book also includes educational exercises for individuals, university classes, or community groups, and an extensive list of recommended readings. The anthology remains unique in presenting a broad array of classic and contemporary readings in this field, each with a concise introduction placing it within the context of this evolving discourse. The Sustainable Urban Development Reader presents an authoritative overview of the field using original sources in a highly readable format for university classes in urban studies, environmental studies, the social sciences, and related fields. It also makes a wide range of sustainable urban planning-related material available to the public in a clear and accessible way, forming an indispensable resource for anyone interested in the future of urban environments"--
Includes bibliographical references and index.
Keywords: City planning; Community development, Urban; Sustainable urban development; ARCHITECTURE / Urban & Land Use Planning; SCIENCE / Earth Sciences / Geography; SOCIAL SCIENCE / Human Geography